Liquid-phase transfer hydrogenation of furfural to furfuryl alcohol on Cu–Mg–Al catalysts - Villaverde, María Magdalena (2014)
The liquid-phase transfer hydrogenation of furfural on Cu-based catalysts was studied. Catalysts were prepared by incipient wetness impregnation (Cu/SiO2) and co-precipitation (Cu–Mg–Al). The effect of metal-support interaction, hydrogen donor, copper loading and temperature on catalytic performance was evaluated. Small particles, strongly interacting with a spinel-like matrix, had higher capability for transferring hydrogen than large ones having low interaction with support. An important increase in reaction rate was observed when temperature was raised from 110 to 150 °C. Thus, it was possible to attain complete furfural conversion to furfuryl alcohol with Cu(40%)–Mg–Al after 6 h at 150 °C.